2010
DOI: 10.2202/1542-6580.2121
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of a Catalytic Micro-Reactor Coupling Endothermic Methane Reforming and Combustion

Abstract: In this study the mathematical modelling of a catalytic microstructured plate reactor for the production of hydrogen was performed in 2D and 3D geometry. The proposed reacting system uses the heat generated by an exothermic reaction (combustion) to sustain endothermic reforming reactions. Therefore, it pertains to those devices useful for producing the feed for fuel cell system for the remote generation of electrical power. However, because of the compactness of the reacting system it can also be considered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…The former are designed as cylindrical devices where heat produced by an inner combustor sustains the endothermic reaction occurring in a thin annular space surrounding it [25][26][27] or, may be constituted by the joining of several rectangular micro-channels arranged in such a way to form a network where the reforming channels are interspersed with the combustion ones [28,29]. The micro-structured plate reactor configuration ( Figure 2) is, instead, generally formed by parallel thin plates delimiting chambers where exothermic and endothermic reactions occur simultaneously but separately in space [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Micro-structured reactors have, generally, inner dimension lower than one millimetre, and more specifically between ten and a hundred micrometers.…”
Section: Recuperative Coupling Reactors Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The former are designed as cylindrical devices where heat produced by an inner combustor sustains the endothermic reaction occurring in a thin annular space surrounding it [25][26][27] or, may be constituted by the joining of several rectangular micro-channels arranged in such a way to form a network where the reforming channels are interspersed with the combustion ones [28,29]. The micro-structured plate reactor configuration ( Figure 2) is, instead, generally formed by parallel thin plates delimiting chambers where exothermic and endothermic reactions occur simultaneously but separately in space [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Micro-structured reactors have, generally, inner dimension lower than one millimetre, and more specifically between ten and a hundred micrometers.…”
Section: Recuperative Coupling Reactors Designmentioning
confidence: 99%
“…Today methane steam reforming represents the principal way to produce hydrogen rich synthesis gas [72][73][74][75][76][77][78][79][80] fulfilling about 50% of the world demand of H 2 [81,82]. It has been reported that the heat required for the endothermic reaction can be supplied through several exothermic reactions in different reactor configurations such as hydrogenation of nitrobenzene for the production of aniline in a tube and shell device [3], combustion of H 2 in a multi-plate reactor [40] or combustion of CH 4 in a variety of systems including honeycomb monolith [50,53], tubular [16], membrane-assisted [67] or catalytic plate reactor [30,33,34,[36][37][38][39]41,[43][44][45][46]. Some examples of couplings of endothermic and exothermic reactions are listed in Tables 1 and 2 in the cases of the absence and of the presence of a selective membrane, respectively.…”
Section: Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two‐dimensional models of microreactors consisting of parallel catalytic plates coupling the SMR and the catalytic combustion of a gaseous fuel in cocurrent flow configuration have been developed also by Stefanidis and Vlachos17–19 to investigate the effects on the microreformer performance of the characteristic length scale, contact time, wall material, fuel, and reforming catalyst. Finally, 3‐D models and computational fluid dynamics (CFD) simulations have been performed by Vaccaro et al24, 25 and Mettler et al12, 26 to study the issue of external heat losses and their influence on the stability and scale‐out of microreactors coupling the SMR and methane combustion reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, producing balanced countercurrent designs that match the rates of heat generation in the exothermic channels and heat consumption in the endothermic channels remains an important issue. [11][12][13][14][15] Previous studies 11,13,15 indicate that the coupling of methane steam reforming with methane combustion in a countercurrent flow arrangement is difficult: the reactant depletion occurs in opposite directions relative to the reactor length. This complicates the efficient synchronization of the reaction rates and therefore the rate of heat generation and heat consumption, with the reactor thermal behavior typically drifting to one of two extremes:…”
Section: Introductionmentioning
confidence: 99%